Effect of sodium dodecylbenzene sulfonate on the dispersion stability of ceramic glaze suspension - Suphapan Satchawan (2018)
Sodium dodecylbenzene sulfonate (SDBS) was used to render the stability of ceramic glaze dispersion which is composed of limestone, feldspar, quartz, kaolin and ferric oxide. The measured zeta potential showed negative values for the systems in deionized water and 0.001 M MgCl 2 media at pH above 2, but a positive value was observed in 0.1M MgCl 2 at pH higher than 6.7. Adsorption of SDBS in aqueous suspensions of ceramic glaze in deionized water and in 0.001 M MgCl 2 , within the concentration range studied, followed both the Langmuir and Freundlich isotherms, but the Freundlich isotherm was more favored. Adsorption of SDBS in 0.1M MgCl 2 corresponded to the Freundlich isotherm. From dispersion stability investigation, SDBS could render the suspension in deionized water and in 0.001 mM MgCl 2 more than in 0.1 mM MgCl 2 . © 2014 Korean Institute of Chemical Engineers, Seoul, Korea.